Development of Motivation Scale for Students in Problem-Based Learning Model - Suryawati, Citra Tectona; Dewantoro, Adi; Agustina, Fita; Puspitarini, Agustina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop an instrument for measuring students' learning motivation in the Problem-Based Learning (PBL) setting as one of the indicators of the success of teaching methods in higher education. The method used was Research and Development following the steps outlined by Plomp & Nieveen (2013). The scale development process followed the DeVellis model. Data analysis in this study included content analysis measured using S-CVI, construct analysis measured using product moment, and reliability analysis measured using Cronbach’s alpha. Content validity was assessed by 4 experts, while construct validity was assessed with a sample size of 312 participants. The developed scale comprises 25 valid and reliable items and meets aspects of relevance, accuracy, and practicality. Therefore, this instrument can be utilized to measure students' learning motivation in problem-based learning contexts. There are four aspects measured through this instrument: choice of task, effort, persistence, and achievement.